2006
DOI: 10.2527/2006.841112x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in morphometry of the small intestine and jejunal sucrase activity during the first nine weeks of postnatal growth in pigs1

Abstract: The objective of this study was to investigate the development of small intestinal size and digestive capacity of the jejunum in growing pigs. The weight, length, surface area, and mucosa weight of the small intestine were measured when pigs were 1, 3, 5, and 9 wk of age. Sucrase and alkaline phosphatase (ALP) activities of the jejunal brush-border membrane, prepared by differential centrifugation and Mg2+ precipitation, were determined at the respective postnatal stages. Body weights increased 7-fold from 2.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 20 publications
6
43
1
Order By: Relevance
“…The Jinhua gilt's intestinal weight and length increased in direct proportion to its body weight. The results are in accordance with previous reports (Aodeola and King, 2006). Jensen et al (1997) also reported that the weight of the small intestine and the length of the small intestine were described as a function of the body weight.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The Jinhua gilt's intestinal weight and length increased in direct proportion to its body weight. The results are in accordance with previous reports (Aodeola and King, 2006). Jensen et al (1997) also reported that the weight of the small intestine and the length of the small intestine were described as a function of the body weight.…”
Section: Discussionsupporting
confidence: 83%
“…The result indicated that, from 35 to 125 days of age, the small intestine of Jinhua gilts undergoes a substantial increase in physical size to accommodate the processing of ingested nutrients. This result is similar to that reported by Adeola and King (2006), who observed that body weight, the weight and length of small intestine, as well as mucosa weight increase with age from 1 to 9 weeks. However, at the same age, Jinhua gilts have a lower weight and length of the small intestine compared with the breed previously reported (Jensen et al, 1997;Aodeola and King, 2006), which suggests that these differences may be attributed to the growth performance of different breeds.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations